Evaluación poblacional de ungulados en las cuencas altas de los ríos Napo y Curaray, Loreto, Perú - Acho Zevallos, Gary Wiliam (2022)
In order to know the population status of ungulates, an investigation was carried out in the upper basins during the Napo and Curaray rivers in June and July 2018. The data was obtained using the linear transect census method, track record, and camera-traps. In the three zones, a total of 512.2 km was covered, where 5 species of ungulates grouped into 2 orders and 3 families were recorded. According to the results of the footprint method, the ungulate species are in a good state of conservation in both basins, Tapirus terrestris and Pecari tajacu were the species with the highest abundance indices; however, the few sightings using the linear transect method and camera traps partially underestimated the results obtained. Regarding the relationship of the ungulate species with the study areas, there were no significant differences (p=0.5); however, T. terrestris, P. tajacu and M. americana were more related to Zones 2 and 3. In conclusion, the present study shows conserved and healthy populations of ungulates, for this reason the expansion of the Airo Communal Reserve is justified. Pai with the purpose of conserving the wildlife of the upper basins of the Napo and Curaray rivers.